Proceedings of MSR-RoManSy 2024 Combined IFToMM Symposium of RoManSy and USCToMM Symposium on Mechanical Systems and Robotics - Larochelle, Pierre; McCarthy, J. Michael; Lusk, Craig P. (Mechanisms and Machine Science, 2024)
VIII, 246 p. 150 illus., 117 illus. in color.